NEW AND INTERESTING RECORDS OF ORTHOPS FIEBER 1858 (HEMIPTERA: HETEROPTERA: MIRIDAE) IN TURKEY (Acta Entomologica Serbica, 2017)
This study is based on material of the genus Orthops Fieber 1858 collected from different localities in Turkey between 1983 and 2014, mostly 2006-2014. In the genus Orthops Fieber, 1858, six species are known from Turkey, including Orthops (Montanorthops) forelii Fieber, 1858, O. (M.) montanus (Schilling, 1838), O. (Orthops) basalis (A. Costa, 1853), Orthops (O.) campestris (Linnaeus, 1758), O. (O.) frenatus Horváth, 1894 and O. (O.) kalmii (Linnaeus, 1758). Orthops (Orthops) frenatus Horváth, 1894, is a new record for Turkish fauna. In this paper, diagnoses, distribution data and illustrated keys to the genera and species are provided. In addition, new localities are added for some species previously reported for Turkey.